Adoption of Modern Technology in Irrigation Projects - Satyanarayana Raju, Indukuri (PREPARE@u® | IEI Conferences, 2021)
Andhra Pradesh state has taken up Polavaram Irrigation Project across Godavari River with a gross storage capacity of 195TMC (utilization-322TMC) which is presently in progress. The main dam components are- Spillway and the main Earth Cum Rock Fill Dam (ECRFD) of 1.75km length and to a height of 48 Mts. The major Challenge is to build ECRF Dam over deep permeable sand bed of about 60-90M. Since conventional Cut off for such dams is problematic, Plastic Concrete Diaphragm cut off wall utilizing modern international technology and machinery was now resorted to by Project. Another challenge that was faced in the project is “building upstream and downstream coffer dams” that has to facilitate construction main ECRF Dam on Godavari River which usually experience flashy floods. In order to overcome permeable sandy foundation strata for the Cofferdams, in place of conventional Z-type Sheet pile cut off of 20M -30M, an alternate foundation soil stabilization technique by Get-Grouting, an international technology was adopted for cofferdams’ foundation to facilitate the construction of main ECRF Dam for early completion of project to accrue its intended benefits. GET-GROUTING soil stabilization: The construction of cofferdam on granular soils involves geo-technical problems of water seepage and potential piping below temporary cofferdams. As per requirement of coffer dam design, Z-Sheet pile steel cut off with 18-20mm thick metal specification for 29M depth for upstream Coffer dam (2.3km length) and 16M depth for downstream Cofferdam of (1.57km length) are needed. There was a problem of availability of 18-20mm thick Z-type Sheet Piles, otherwise to import of which likely will cause delay in the project in construction. An alternate Get- Grouting Soil stabilization for cofferdams was proposed being the modern technology. In order to control the seepage below coffer dams, Jet Grouting technique has been chosen based on overall exit gradient and duly conducting seepage analysis. PASTIC CONCRETE DIAPHRAGM Cut off Wall for Earth Cum Rock Fill Dam: A Diaphragm wall is a civil engineering technique used to build reinforced concrete walls in areas of soft earth or sand close to open water, or with a high groundwater table. This technique is typically used to build diaphragm (water-blocking) walls in open cuts, to lay foundations and arrest seepage through foundation. This modern technology was adopted for execution of main Earth Cum Rock Fill Dam of 48M height and 1.75 km long across Godavari River having deeper sandy bed needing 60-90 mts deep as Cut off Wall (COW) with embedment in to impervious strata to overcome the technology challenge in the project. For smaller depth of impervious strata, conventional cut off trench beneath Earth dam is a general practice. But in the present case an order of 90 Mts cut of is to be done where seepage permeability is an about 3-6 cum per day per meter width. In order to overcome this technical problem, Plastic Concrete Diaphragm wall technology with deployment of imported machinery was resorted to. The Polavaram ongoing Irrigation project across Godavari River in Andhra Pradesh has been the conceived over 8 decades back and delayed due to Geo-Technical Engineering Problems. Eminent international experts viz. Dr Karl Terzaghi, Professor of Soil Mechanics; Dr JL Savage Chief Engineer from USA and Sir Murdole Macdonald, a famous Consulting Engineer (ASWAN Dam) of London have either visited site or imparted technical advice on foundation problems of the project. Finally the project is becoming a reality with adoption modern technology of this century by overcoming foundation problems with adoption of JET-Grouting soil stabilization for coffer dam foundations and Plastic Concrete Diaphragm Cut Off Wall (COT) beneath Earth Cum Rock Fill (ECRF) Dam during 2019.This Multipurpose Dam is becoming a reality and making it possible by adoption of Modern Technology in civil engineering construction to benefit seven (7) lakh hectares new command and Hydro-Power generation of 960 MW to enhance GDP of not only the State but also the Nation.